2021
DOI: 10.1097/cin.0000000000000771
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' Strategies to Prevent and/or Decrease Work-Related Technostress

Abstract: Although there is evidence of the impact of technostress on nurses' physical and psychological well-being, there is no clear understanding of what strategies are used by nurses to prevent/decrease work-related technostress. Thus, we aim to map existing literature that describe the strategies used by nurses to prevent or decrease work-related technostress. This review followed the methodology proposed by the Joanna Briggs Institute for scoping reviews. Data analysis, extraction, and synthesis were performed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 23 publications
(68 reference statements)
0
7
0
Order By: Relevance
“…As with a recent scoping review on nurses’ strategies to prevent technostress, no studies on prevention measures or strategies were identified in this scoping review [ 37 ]. Given the lack of studies addressing primary, secondary or tertiary prevention or technostress interventions, merely first approaches based on the findings presented in this review can be suggested.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As with a recent scoping review on nurses’ strategies to prevent technostress, no studies on prevention measures or strategies were identified in this scoping review [ 37 ]. Given the lack of studies addressing primary, secondary or tertiary prevention or technostress interventions, merely first approaches based on the findings presented in this review can be suggested.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, far less research has investigated how to address these causes or deal with adverse effects resulting from technostress [ 5 , 9 ]. Specifically, there is considerably less scientifically substantiated evidence on adequate coping strategies [ 5 , 22 , 27 , 35 ] or prevention measures [ 36 , 37 ]. Apart from more specific reviews which could not identify strategies to prevent technostress among nurses [ 37 ] or focused on coping with discrepant information technology events [ 35 ], there is no comprehensive systematic overview of research on how to prevent and cope with technostress yet.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nine of the 12 new items aligned with the following themes: the use of technology, workload, and not feeling valued. These findings were not surprising as recent advances in technology have significantly changed nursing practice and contributed to additional job demands and responsibilities, which consequently leads to higher levels of stress (Lucena et al, 2021; Moustaka & Constantinidis, 2010; Yen et al, 2019). Studies have also reported an association between nurses not feeling valued, lower levels of satisfaction, and higher levels of occupational stress (Prasad et al, 2021; Waltz et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Nursing practice has changed substantially over the past 20 years, which presents new potential sources of occupational stress. Most notably, technology has transformed nursing practice and healthcare delivery, nursing has integrated the use of the electronic health record into daily patient care, new nursing specialties have been introduced, and some nursing roles have been entirely redesigned (Lucena et al, 2021; National Academies of Sciences, Engineering, & Medicine, 2021; The Journal of mHealth, 2019). While the aforementioned changes in nursing practice are known, and these changes have been shown to contribute to stress in nursing, it is not clear if these occupational stressors are adequately captured in existing stress measures, specifically the NSS and ENSS, that were developed decades ago.…”
Section: Stress and Stress Measurement In Nursingmentioning
confidence: 99%